Biotransformation of Meloxicam by Cunninghamella blakesleeana: Significance of Carbon and Nitrogen Source - Shyam Prasad, Gurram (Springer-Verlag, 2011)
Influence of carbon and nitrogen source, on biotransformation of meloxicam was studied by employing Cunninghamella blakesleeana NCIM 687 with an aim to achieve maximum transformation of meloxicam and in search of new metabolites. The transformation was confirmed by HPLC and based on LC–MS–MS data and previous reports the metabolites were predicted as 5-hydroxymethyl meloxicam, 5-carboxy meloxicam and a novel metabolite. The quantification of metabolites was performed using HPLC peak areas. The results obtained indicate that glucose as carbon source, ammonium nitrate as nitrogen source, were found to be optimum for maximum transformation of meloxicam. The study suggests the significance of these factors in biotransformation of meloxicam using microbial cultures. The fermentation was scaled up to 1 l level.